A preservação digital do patrimônio cultural no ecossistema empreendedor à luz da Lei Geral de Proteção de Dados - LGPD - Carvalho, Vagner da Silva de (2021)
This research offers objectives, as main objective, to develop a primer on the concepts and steps that guide the realization of digital production and preservation taking into account the use of sensitive data from the entrepreneurial ecosystem methodology. Through this vector, the specific objectives were defined as: To analyze the booklets of the Requirements Model for Computerized Systems of Archival Management of Documents; Identify how recommendations for digital production and preservation environments using the entrepreneurial ecosystem methodology; Develop a model that connects the recommended specifications according to the LGPD. Consistent application, from the perspective of a bibliographic research, the search for primary sources, bibliographies, publications and booklets in particular of CONARQ, Law No. 13.709 and Law No. 8.159. In addition, there was an exploratory phase, with a survey of the perceptions of academics and professors of the Bachelor of Archives course at the Federal University of Santa Maria (UFSM). The instrument used was a questionnaire available online, sent via email and social media. From the readings and the results obtained, it was possible to develop the product, a booklet with concepts and suggestions for approaching the issue for entrepreneurs, thus achieving the objectives. The results suggested the need to update the Archives Law, which has been carried out in slow stages, initiated as a result of directed groups of professors and researchers in the archival area, and an insertion of themes related to digital preservation in its new version. The need for education, knowledge and social concerns with this topic was highlighted. With regard to financial capital, the results showed accessibility for investments in the area. In the field of support institutions, CONARQ, the Technical Chamber of Electronic Documents and the associations of archivists were essential in this field. The fundamental suggestion for guaranteeing best practices in the archival field was the creation of a professional council.